Green Climate Control - Tatiana Armijos Moya (A+BE: Architecture and the Built Environment)
Several studies have demonstrated the potential of botanical biofiltration and phytoremediation to remove indoor pollutants and improve overall comfort. However, there is a lack of evidence on how indoor greenery affects the Indoor Environmental Quality (IEQ), particularly on Indoor Air Quality (IAQ). The main goal of this research project was to explore and evaluate the efficacy of an active plant-based system in terms of IAQ and being able to answer the main research question: “Can an active plant-based system improve the Indoor Air Quality (IAQ)?” This was achieved through laboratory studies of several plant-based systems, including chemical, physical and sensorial evaluations as well as qualitative and quantitative assessments. Some of the outcomes of this research are described below: